2008
DOI: 10.1007/s12034-008-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of silver molybdate nanowires, nanorods and multipods

Abstract: Silver molybdate nanowires, nanorods and multipods like structures have been prepared by an organic free hydrothermal process using ammonium molybdate and silver nitrate solutions. The powder X-ray diffraction (PXRD) patterns reveal that the silver molybdate belongs to anorthic structure. The thickness, 200-500 nm, for silver molybdate nanorods/wires and 2-5 µm for microrods are identified from SEM images. UV-visible spectrum of silver molybdate nanorods/nanowires shows maximum absorbance at 408 nm. Photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Molybdate compounds are important materials for a range of technological applications due to their chemical stability [1,2], which make them suitable to be used in electrochemical devices [3], microwave-based devices [4], optical fibers [5], light emitters [6,7], scintillators [8], sensors [9], and catalysts [10]. In particular, the silver molybdate compound (Ag2MoO4) belongs to the class of molybdates and tungstates with A2 + B 6+ O4 formula, where A is univalent metal and B is molybdenum or tungsten.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molybdate compounds are important materials for a range of technological applications due to their chemical stability [1,2], which make them suitable to be used in electrochemical devices [3], microwave-based devices [4], optical fibers [5], light emitters [6,7], scintillators [8], sensors [9], and catalysts [10]. In particular, the silver molybdate compound (Ag2MoO4) belongs to the class of molybdates and tungstates with A2 + B 6+ O4 formula, where A is univalent metal and B is molybdenum or tungsten.…”
Section: Introductionmentioning
confidence: 99%
“…The silver molybdates can be obtained by different methods of synthesis [12][13][14][15][16][17][18][19][20][21][22][23][24][25] in various morphologies [26,15,27,28,7,29,20,30], which make this compound the subject of several investigations, including the study of structural transitions by means of differential thermal analysis (DTA) [2], X-ray diffraction (XRD) [27,6], Raman spectroscopy [1,27,6,31], surfaceenhanced Raman spectroscopy [27,28] and absorption and emission spectroscopy [6,28,32,7]. However, the room temperature structure of the Ag2MoO4 crystal exists in two different forms namely as α-Ag2MoO4 (tetragonal) and β-Ag2MoO4 (cubic) [33].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been made to obtain Ag 2 MoO 4 ‐ based materials as flower‐like, nanoparticles and wire‐like nanostructures . Low‐dimensional Ag 2 MoO 4 nanostructures have been obtained by Nagaraju et al who reported the synthesis of nanorods/nanowires/multipods and the photoluminescence of microrods; while Feng et al have been synthesized as ultra long orthorhombic silver trimolybdate nanowires. Qian et al have reported the microwave‐assisted hydrothermal synthesis of cube‐like AgAg 2 MoO 4 with visible‐light photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…where I(t) is intensity, τ 1 , τ 2 and τ 3 Highly sharp and intense lines in the region 300-550 nm are attributed to intraconfigurational f-f transition of Eu 3+ . Within these transitions, the ( 7 F 0 → 5 L 6 ) at 395 nm and ( 7 F 0 → 5 D 2 ) at 465 nm are the most intense ones and the less intense peaks were observed at 361 nm ( 7 F 0 → 5 D 4 ), 380 nm ( 7 F 0 → 5 G 2 , 5 G 3 ), 414 nm ( 7 F 0 → 5 D 3 ), and 533 nm ( 7 F 0 → 5 D 1 ).…”
Section: Figure 2: (A) Emission Spectrum and (B) Cie Index Diagram Fomentioning
confidence: 99%